Dataset: A decadal perspective on permafrost thaw slump disturbances on Arctic upland lakes in the Mackenzie Delta region (Northwest Territories, Canada) - Thienpont, Joshua; O'Hagan, Claire; Hoskin, Grace; Kokelj, Steve; Korosi, Jennifer (2022)
Data and method detection limits for water chemistry analyses carried out in June/July 2017. 48 lakes we resampled (previous chemistry data collected in late August 2005) to assess limnological changes due to permafrost thaw slumping. These data are compared to remotely sensed changes in thaw slumps. Retrogressive thaw slumps are the dominant thermokarst landscape disturbance in regions of ice-rich permafrost. The impact of thaw slumps on the water and sediment chemistry and aquatic biology of lakes of the Tuktoyaktuk Coastlands has been explored for almost 2 decades. This corresponds to a period of accelerated warming and an intensification of thaw-driven mass wasting. Past research in the region provides a basis for developing a relatively long-term perspective on limnological changes associated with thaw slump activity. Here we revisit lakes sampled previously, to investigate if water chemistry parameters have changed with thaw-related catchment characteristics. We combined re-sampling of water chemistry (48 lakes) with remotely-sensed image-derived characterization of thaw slump activity (66 lakes) to provide a decadal perspective on changes in the Mackenzie Delta region. Our data showed that four thaw slumps that were stable in 2005 had active slumps that had reinitiated, five lakes with active slumps in 2005 had since stabilized, and two lakes previously classified as reference now have active slumping. Water chemistry variables associated with slump activity (e.g., conductivity, major ion concentrations) were slightly lower in most lakes (likely due to sample timing), but increased in lakes with the greatest thaw slump growth. In several lakes with slumps that had stabilized over the last decade, conductivity decreased >20%, suggesting recovery may be occurring. This research provides a decadal perspective on the linkage between intense landscape disturbance and limnological change in one of the most rapidly warming regions on Earth.